Microbiological Characteristics, Risk Factors, and Short-Term Mortality of Carbapenem-Resistant Enterobacteriaceae Bloodstream Infections in Pediatric Patients in China: A 10-Year Longitudinal Study - Liang Y; Zhao C; Lu Y; Liao K; Kong Y; Hong M; Li L; Chen Y (Infection and Drug Resistance)
Yujian Liang,1,* Chenfeng Zhao,2,* Yuhang Lu,3,* Kang Liao,2 Yannan Kong,4 Mengzhi Hong,2 Liubing Li,2 Yili Chen2 1Department of Pediatric Intensive Care Unit, The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, Guangdong, 510080, People’s Republic of China; 2Department of Laboratory Medicine, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, 510080, People’s Republic of China; 3Zhongshan Medical School, Sun Yat-sen University, Guangzhou, Guangdong, 510080, People’s Republic of China; 4Department of Laboratory Medicine, the Nanhai’s Fifth People’s Hospital of Foshan, Foshan, Guangdong, 528231, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yili Chen; Liubing Li, Department of Laboratory Medicine, the First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, 510080, People’s Republic of China, Email chenyli3@mail.sysu.edu.cn; lilb8@mail.sysu.edu.cnBackground: Carbapenem-resistant Enterobacteriaceae (CRE) is rapidly becoming a major threat to hospitalized children worldwide. The purpose of this study was to summarize etiological characteristics and identify risk factors relevant to CRE bloodstream infection (BSI) and short-term mortality among pediatric patients in China.Methods: In this study, we included 370 inpatients ≤ 17 years old with BSI caused by Enterobacteriaceae in China from January 2013 to December 2022. By collecting data on demographics, etiological features, and clinical outcomes, we conducted an in-depth analysis.Results: Among the 370 BSI patients with infections caused by Enterobacteriaceae, 35 patients (9.46%) were caused by CRE. Among these CRE strains, Klebsiella pneumoniae (49.46%) was the most important pathogen of BSI in pediatric patients, followed by Escherichia coli (31.62%) and Enterobacter cloacae (5.95%). The most frequent carbapenemase was NDM (23/35, 65.71%), followed by KPC (8/35, 22.86%). The overall 28-day mortality rate of children with an Enterobacteriaceae BSI episode was 1.89% (7/370), of which CRE BSI patients (3/35, 8.57%) were significantly higher than CSE patients (4/335, 1.19%, P < 0.001). Congenital malformation (OR: 8.162, 95% CI: 3.859– 16.680, P < 0.001) and catheter-related (OR: 6.645, 95% CI: 3.159– 13.28, P: < 0.001) were associated with the development of CRE BSI in pediatric patients. A multivariate analysis showed that the infection of CRE (OR 7.758, 95% CI 1.869– 29.62, P = 0.021) were independent risk factors for 28-day mortality of Enterobacteriaceae BSI. When the MIC of any carbapenems was ≥ 8 μg/mL, the mortality rate in the ICU was higher (P < 0.05).Conclusion: Congenital malformation, previous cephalosporin/carbapenems administration, and catheter-related conditions were closely related to the development of CRE BSI. The mortality rate of CRE BSI was higher. NDM was the predominant carbapenemase-producing mechanism in children.Keywords: carbapenem-resistant Enterobacteriaceae, bloodstream infection